Zero waste engineering - Khan, M. M.; Islam, Rafiqul, 1959-; Wiley InterScience (Online service) (Hoboken, N.J. : John Wiley & Sons ; Salem, Mass. : Scrivener Pub., 2012)
"The idea of "Zero-Waste Engineering" has been developing over years, in many areas of engineering, such as energy production (renewable energy), construction (green buildings), and many others. This book is a huge step in the continued march toward truly sustainable engineering practices. This book presents methods in various areas for sustainability purposes, such as new mathematical models, recyclable material selection, and renewable energy. Engineers and scientists of all industries will benefit from these principles of zero-waste engineering and how it applies to construction, energy production, and many other areas of engineering"--
"Explores new scientific principles on which sustainability and zero-waste engineering can be based Presents new models for energy efficiency, cooling processes, and natural chemical and material selection in industrial applications and business - Explains how "green buildings" and "green homes" can be efficiently built and operated with zero waste - Offers case histories and successful experiments in sustainability and zero-waste engineering"--
Front Matter -- Introduction -- A Delinearized History of Time and Its Impact on Scientific Cognition -- Towards Modeling of Zero Waste Engineering Processes With Inherent Sustainability -- The Formulation of a Comprehensive Mass and Energy Balance Equation -- Colony Collapse Disorder (CCD): The Case for a Science of Intangibles and Zero Waste Engineering -- Zero Waste Lifestyle with Inherently Sustainable Technologies -- A Novel Sustainable Combined Heating/Cooling/Refrigeration System -- A Zero Waste Design for Direct Usage of Solar Energy -- Investigation of Vegetable Oil as the Thermal Fluid in a Parabolic Solar Collector -- The Potential of Biogas in the Zero Waste Mode in the Cold-Climate Environment -- The New Synthesis: Application of All Natural Materials for Engineering Applications -- Sustainability of Nuclear Energy -- High Temperature Reactors for Hydrogen Production -- Economic Assessment of Zero Waste Engineering -- Conclusions and Recommendations -- References -- Index -- Also of Interest.
Includes bibliographical references and index.
Print version record.
Keywords: Waste minimization; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Waste minimization; Electronic books; Electronic books